2011
DOI: 10.1371/journal.pgen.1002201
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Phosphatidic Acid in the Formation of “Supersized” Lipid Droplets

Abstract: Lipid droplets (LDs) are important cellular organelles that govern the storage and turnover of lipids. Little is known about how the size of LDs is controlled, although LDs of diverse sizes have been observed in different tissues and under different (patho)physiological conditions. Recent studies have indicated that the size of LDs may influence adipogenesis, the rate of lipolysis and the oxidation of fatty acids. Here, a genome-wide screen identifies ten yeast mutants producing “supersized” LDs that are up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
361
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 319 publications
(390 citation statements)
references
References 43 publications
(75 reference statements)
26
361
3
Order By: Relevance
“…Higher PA levels in S-KO compared with gS-KO testes may be associated with a diluting effect of normal lipids present in the Leydig cells of gS-KO mice, which express low levels of seipin. Elevated PA levels have also been reported from seipin-deleted yeast and seipin-KO Drosophila (27)(28)(29)(30). We speculate that seipin may participate in the regulation of PA metabolism in testis, thereby controlling LD morphology and formation.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Higher PA levels in S-KO compared with gS-KO testes may be associated with a diluting effect of normal lipids present in the Leydig cells of gS-KO mice, which express low levels of seipin. Elevated PA levels have also been reported from seipin-deleted yeast and seipin-KO Drosophila (27)(28)(29)(30). We speculate that seipin may participate in the regulation of PA metabolism in testis, thereby controlling LD morphology and formation.…”
Section: Discussionsupporting
confidence: 51%
“…The disturbance of PL homeostasis in spermatids could affect the stability of intercellular bridges and hence, impair the separation of matured spermatids, leading to massive accumulation of S-KO and gS-KO spermatids in bundle-like structures. Previous studies have shown that elevated PA enhances the formation of very large LDs (27). PA is a cone-shaped lipid that alters the membrane curvature and can promote membrane fusion events.…”
Section: Discussionmentioning
confidence: 99%
“…SEIPIN also regulates the metabolism of phosphatidic acid (PA) at the LD-ER contact, acting as a scaffolding protein recruiting PA-metabolism enzymes such as LIPIN1 and AGPAT2 [16,17] as well as controlling PA levels by inhibiting GPAT [18]. In addition to being the biosynthetic precursor of phospholipids and TAGs, PA is a cone-shaped phospholipid that facilitates LD fusion [19,20] and could be accommodated in the regions of negative membrane curvature associated to LD budding and LD-ER connections [21]. The downregulation of the ER enzymes CDS1 or CDS2, which consume PA to form CDP-DAG, increases PA levels in the ER but also in LDs, an effect accompanied by LD enlargement and also observed with the downregulation of LIPIN1 [22].…”
Section: The Er In Ld Biogenesis and Growthmentioning
confidence: 99%
“…Although LD-LD coalescence is rarely observed in physiological conditions [31], it occurs spontaneously as a result of altered phospholipid composition in the LD monolayers, either by deficient levels of LD-stabilizing PC [32] or by accumulation of the fusogenic PA [20]. This fusion will result in a decrease in the total LD surface/volume ratio, but the fate of the spare membrane components is not well understood.…”
Section: Ld-ld Fusionmentioning
confidence: 99%
“…Phosphatidic acid, preferred substrate for DDHD1 and DDHD2, is essential for lipid droplet assembly. 24 The acetyl-CoA transporter SLC33A1 located in the ER membrane and required for the formation of O-acetylated gangliosides is mutated in SPG42. Defects in the metabolism of complex lipids cause at least four more HSP subtypes: in SPG39 the deacetylation of phosphatidylcholine, the major membrane phospholipid, is defective due to mutations in phospholipase B/neuropathy target esterase (PNPLA6), 7 mutations in fatty acid-2 hydroxylase (FA2H) affect synthesis of 2-hydroxysphingolipids in 25 and CYP2U1 mutations in SPG49 lead to disturbed o-and w-1 fatty acid hydroxylation.…”
Section: Ddhd2 (Spg54)mentioning
confidence: 99%